STATISTICAL REASONING TENTANG KEBIJAKAN SATU ANAK PER KELUARAG DI NEGERI TIRAI BAMBU ( CINA) - Hermawan, Toto; Fajarini, Nuria Mahdra; Utami, Nurni (Fakultas Keguruan dan Ilmu Pendidikan Universitas Cokroaminoto Yogyakarta, 2022)
This study attempts to explain what distribution of opportunities is in accordance with population growth if a family must have sons and evaluate policies based on the data obtained. The distribution of opportunities according to population growth if a family must have sons is a geometric distribution. For n families, the binomial distribution is used to measure the success rate of the government. If the chances of having a baby boy are high, then the chances of the one-child policy will be successful. In addition, the one-child policy in China was a policy implemented during the Deng Xiaoping administration in 1979 until it was finally abolished at the end of 2015. The decision to abolish this policy is of course a very interesting matter because this policy has been implemented for more than three decades and has succeeded in driving economic growth and improving the standard of living of the Chinese people. After more than three decades of implementation, various social and economic impacts have been felt by China as a result of the one-child policy. The low fertility rate in China, the imbalance of the sex ratio, and the aging population are new problems facing China because of the implementation of this policy. Taking into account these effects, the Chinese government officially abolished the one-child policy and implemented a new policy that allows every couple in China to have two children